Books (Res Medica, 2014)
• Human Nutrition and Dietetics. Davidson and Passmore. E. & S. Livingstone Ltd., Edinburgh.• Simpson and Syme of Edinburgh. John A. Shepherd. Livingstone. 50s.• Notes for the Guidance of Parents of Diabetic Children. J. W. Farquhar.• Early Difficulties with Young Families. Charlotte Himsworth. H. K. Lewis. 45s.• Modern Trends in Obstetrics. Edited R. J. Kellar. Butterworth. 64s.• British Medical Bulletin. “ Immunization Against• Infectious Diseases”. Volume 25, Number 2, May 1969. £2.• Attachment of the Young. F. V. Smith. Oliver & Boyd. 7s. 6d.• Modern Trends in Gynaecology. Edited R. J. Kellar. Butterworth. 64s.• Primer of Histopathological Technique. Geoffrey G. Brown. Butterworth. 52s.